PENGATURAN PARKIR KENDARAAN MASUK/KELUAR AREA PARKIR DAN MEMBANTU PENGEMUDI SAAT PARKIR BERBASIS MIKROKONTROLLER - Laxsmy Devy (Elektron : Jurnal Ilmiah, 2009)
Many parking area still use manual system such as ticketing, parking position, etc. Nowadays, this system can be control easier using microcontroller. In this control system, infra red and photodiode are used to inform when car come and out to parking area. Another sensor, ultrasonic, is used to help driver to park the car safely. Alarm will warn the driver if the position of the car broke the limitation of safety range to park. In another hand, the empty parking areas are display in LCD and related with portal which opened when the empty parking area still available and close if it full automatically. Microcontroller is used to control sensor, LCD and portal